The Effect of Harmonic Distortion in Capacitive and Inductive Loads on the Performance of Electrical Grids in Huge Projects (FADEN Spectrum Phenomenon - an example) (Latakia University Journal -Basic Sciences Series, 2023)
This research deals with the study, analysis and treatment of a strange phenomenon that suddenly appeared during the installation of a huge screen belonging to FADEN Spectrum Company on one of the huge towers in the city of Al-Khobar in the Kingdom of Saudi Arabia with area of 2000 m2, consisting of 2000 cabins and feeding 2000 cells, each cell having an area of 1 m2. This phenomenon includes two things: The first is the appearance of an annoying noise emanating from the main feed box (MDB), and the noise increases exponentially with the increase in lighting intensity to become a noise of 90 dB at 60% illumination and 155 dB at 100% illumination. As for the second, most surprising thing, it is the cables getting hot at a point that exiting from the panel ceiling only, where the temperature reached #83C, noting that the cables before and after this point were not affected by this temperature at all, so that temperature was #28C before the entry point, and the same temperature after the exit point, while the iron metal of the panel ceiling was clearly affected, that also recorded #83C.